(untitled) (E Conference Zone, 2022)
in order to organize effective anti-epidemic measures aimed at preventing the development of acute intestinal diseases, the dynamics of acute intestinal infections in the Republic of Karakalpakstan over the past 5 years have been studied taking into account the existing regional features.